Need to Organize the Neurological Unit at the Faculty of Medicine at the University of San Marcos - Jerí, Raúl (1963)
In order to improve teaching , both student and professional level . the creation of the Neurological Unit of the Faculty of Medicine is proposed. This section shall consist of a group of teachers dedicated to neuroscience , evelop in various teaching hospitals of the Faculty, and assume educational , welfare and research responsibilities. With regard to education, the unit will assume full responsibility for the following Courses : neuroanatomy , neurophysiology , neuropathology , Neurosemiología , Nosography Neurological Clinical Neurology and Neurosurgery . Teaching is conducted in the various years of study, from 19 to 69 . Later the unit will organize teaching and residences , according to the Graduate School , Neurological three specialties : Neuropathology , Neurology and Neurosurgery . In relation to those services, the unit will operate initially in the Dos de Mayo (San Luis Sala, medical and surgical wards , clinics ) Hospital, and then extend their care activities to other hospitals. It is understood that care work are inseparable from the teachers, both student and professional in the performance of this unit . With regard to research, the unit will indicate annually topics under study, after referring to the respective projects Research Council of the Faculty of Medicine . As urgent officially recognize the unit , since in practice has started operation since 1962 , it would be desirable that the faculty approve this project and to call competition to fill the existing vacancies of Teachers Top of Neuropathology , Neurology and Neurosurgery . The organization of this unit has a strictly functional nature , respecting the existing structure of departments in the Faculty of Medicine.